Interactive Learning Media Duck Race on the Online Stopwatch Website to Increase Motivation to Learn Islamic Religious Education - Febriliana Rika Anjani; Ehwanudin; Adi Wijaya (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This research is motivated by low student learning motivation in Islamic Religious Education (PAI) lessons, caused by the use of conventional learning methods and the lack of use of interactive learning media. This condition results in low student activity, attention, and participation in the learning process. This study aims to determine the application of the Duck Race interactive learning media on the Online Stopwatch website, analyze changes in student learning motivation, and identify supporting factors and obstacles in its use. This study used a Classroom Action Research (CAR) approach, implemented in two cycles: Cycle I and Cycle II, with seventh-grade students of SMP Islam Plus Hidayatut Thullab, Central Lampung as the subjects. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis employed an interactive analysis model that encompasses data reduction, data presentation, and conclusion drawing. The results showed that the application of the Duck Race interactive learning media increased student learning motivation from Cycle I to Cycle II. In Cycle I, student learning motivation began to increase but was not evenly distributed. However, in Cycle II, significant improvements were seen, indicated by increased student activity, attention, enthusiasm, and participation in learning. Furthermore, the use of this media can create a more active, engaging, and enjoyable learning environment. The successful implementation of this learning media is supported by the availability of technological facilities, teacher creativity, and student enthusiasm. However, there are challenges in its implementation, such as limited learning time and internet connection stability. Therefore, the interactive learning media Duck Race can be an effective, innovative alternative to increase student motivation in Islamic Religious Education (ISE)..